Kepemimpinan Sekolah Dasar di Masa Covid-19 - Ana Fitrotun Nisa; Nurwiarsih Nurwiarsih (Mafapress bekerja sama dengan Prodi PGMI Fakultas Tarbiyah IPMAFA Pati, 2021)
The coronavirus disease (covid-19) pandemic demands all aspects including the world of education to carry out lockdowns or self-quarantine in an effort to minimize the spread of covid-19. This forces policy makers in schools to be able to adapt to various alternative activities that are adapted to existing developments. This article aims to describe the leadership of primary schools during the Covid-19 period which was carried out at SD Lazuardi Tursina Banyuwangi. The research method used is descriptive qualitative method. The subjects of this study were the director, principal and teachers at SD Lazuardi Tursina Banyuwangi. The data collection technique is done by interview, observation and documentation. The data analysis technique is done by reducing the data, presenting the data and drawing conclusions. The results showed that the leadership carried out in the management of SD Lazuardi Tursina during the covid-19 period included: 1) simplifying the curriculum; 2) coordination and intense discussion between directors, principals and teachers regarding the adjustment of learning techniques, strategies, models and methods; 3) more flexible budget management; 4) continuous evaluation of policies that have been implemented; 5) good communication between schools and parents; and 6) good cooperation with various aspects.